INCREASING THE ANTI-FRICTION CHARACTERISTICS OF CAR AIR CONDITIONER COMPRESSOR PISTON SEALS - DYKHA, OLEKSANDR; SVIDERSRKYI, VLADYSLAV; HOLENKO, KOSTIANTYN (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The shortcomings that occur when using fluoropolymers in the piston seal friction unit - the air conditioner compressor cylinder of the car are analyzed. It has been determined that a physical modification method has been developed in world practice to eliminate the drawbacks of fluoropolymers, which is based on creating composite materials by introducing finely dispersed fillers (graphite, coke, metal oxides, carbon fiber, nanopowders, etc.) into polytetrafluoroethylene (PTFE). The prospective methods for modifying polytetrafluoroethylene and the requirements for its fillers are discussed. The use of polymer-oligomeric matrices and the principle of multilevel modification are quite promising directions for creating multi-purpose tribotechnical composites based on fluoroplastics. Comparative studies of the mechanical, thermophysical, and anti-friction properties of thermoplastics reinforced with carbon and glass fibers have shown that carbon fiber reinforced composites outperform thermoplastics reinforced with glass fibers in terms of bending modulus by a factor of two, thermal conductivity by a factor of 2-3, and have 2 times less deformation under creep conditions. This prompted the development and study of self-lubricating materials based on fluoroplastics modified with combined fillers. It has been established that when developing anti-friction materials based on fluoroplastics, it is necessary to select polymer-filler systems that would form intermediate films on the metal during friction using one of the filler or polymer mechanisms. The implementation of the second mechanism provides more wear-resistant friction pairs, and for improving the adhesion of such an intermediate film to metal, the composite must contain a light abrasive to facilitate the formation of a juvenile surface that is active to the dispersing matrix. Conducted experimental studies confirmed the advantages of anti-friction composite fluoroplastic materials modified with combined fillers: carbon and glass fiber, carbon fiber and copper or lead oxide powder for the piston seal friction unit - the compressor cylinder of the car air conditioner.